Betwixt and between identities: Liminal experience in contemporary careers. (2016) - Ibarra, Herminia; Obodaru, Otilia
Abstract: Liminality, defined as a state of being betwixt and between social roles and/or identities, is the hallmark of an increasingly precarious and fluctuating career landscape. The generative potential of the liminality construct, however, has been restricted by six key assumptions stemming from the highly institutionalized nature of the rites of passage originally studied. As originally construed, liminality (1) implied both an objective state and the subjective experience of feeling betwixt and between, and was (2) temporary, (3) obligatory, (4) guided by elders and/or supported by a community of fellow liminars, (5) rooted in culturally legitimate narratives, (6) and led to a progressive outcome, i.e., the next logical step in a role hierarchy. By recasting these assumptions as variables, we improve the construct's clarity, precision, and applicability to contemporary liminal experiences that are increasingly under-institutionalized. We illustrate the utility of our updated conceptualization by arguing that under-institutionalized liminality is both more difficult to endure and more fertile for identity growth than the highly institutionalized experiences that gave rise to the original notion. Drawing from adult development theory, we further propose that for under-institutionalized experiences to foster identity growth, the identity processes involved need to be more akin to identity play than identity work. We discuss the theoretical implications of our ideas for research on liminality, identity, and careers.